Key Factors Influencing Male Undergraduate Students’ Behavioral Intentions Towards Mobile Library Platforms in Chengdu, China - Xin, Ying (Scholar: Human Sciences, 2025)
Purpose: This study aimed to examine the primary factors that influence the behavioral intention of male undergraduate students toward mobile library platforms (m-library) in private universities in Chengdu, China. The key variables are system quality, perceived ease of use, perceived interaction, perceived usefulness, use attitude, information technology, social influence, and behavior intention. Research design, data, and methodology: The study adopted a quantitative technique, utilizing a questionnaire to acquire data from the sample group. The questionnaire’s content validity and reliability were evaluated via IOC and pilot testing before distribution. Confirmatory factor analysis (CFA) and structural equation modeling (SEM) were used to analyze the data, evaluate the model’s adequacy, and construct a causal relationship between variables to test the hypothesis. Results: The study’s findings indicate that the conceptual model effectively forecasted private college students’ behavioral intention to use MLPs. Information technology, perceived usefulness, and attitude towards use are significant factors that influence the behavioral intention to use MLP. Conclusions: Behavioral intention predictions are most directly influenced by attitudes. Therefore, this study suggests that MLP developers in private colleges and universities be focused on using attitudes targeting female students to encourage usage patterns and behavioral intentions.